Analisis Tindak Pidana Perbankan Menurut UU Nomor 10 Tahun 1998 - Susanti , Susan; Ayu , Agilia Putri; Suryani, Reni; Yollandah, Yollandah; Putri , Intan Dwi (Universitas Dehasen Bengkulu, 2024)
A banking crime is a criminal act by using a bank institution as a means and or a bank institution as the object. Banking crimes are included in corporate crimes. This study aims to describe the legal concept of banking crimes in Indonesia and corporate legal liability in banking crimes. This research is normative. The primary legal materials used are the 1945 Constitution of the Republic of Indonesia; the Criminal Code; Law Number 8 of 1981 concerning the Criminal Procedure Code, Law Number 10 of 1998 concerning Banking Amendments to Law Number 7 of 1992. According to Law Number 10 of 1998, criminal acts in the banking sector consist of three twelve (13) kinds. Of the thirteen kinds of criminal acts in the banking sector, they are grouped into, namely: 1). Criminal acts related to licensing, 2). Crime related to bank secrecy, 3). Criminal acts related to bank supervision and development, 4). Criminal acts related to attitudes and/or actions taken by management, employees, affiliated parties, and bank shareholders. Based on Law 10 of 1998, corporations are not subject to criminal law. This means that if a criminal act occurs in the banking sector, the bank as a corporation cannot be held criminally responsible. The concept of the Banking Law is in line with the concept of the Criminal Code which does not yet recognize corporations as a subject of criminal law. The Banking Law can be classified into statutory regulations in the field of administrative law which contain criminal sanctions. However, the Banking Law does not stand alone in solving banking crime problems, because the scope of banking crimes is quite broad. It does not only cover banking crimes committed by bank insiders, but also includes crimes committed by people outside the bank, who have close links with the banking industry. These laws and regulations are specific in nature, which in their provisions can be a reference to problems related to banking crimes. The law that supports the Banking Law in dealing with the problem of banking crimes is Law No. 25 of 2003 concerning the Crime of Money Laundering. This law has adopted the concept of corporate legal liability so that it is possible for banks to be punished, provided that a corporation can be charged with criminal